Peningkatan Disolusi Asam Mefenamat Melalui Kokristalisasi dengan Para-Aminobenzoic Acid Menggunakan Metode Liquidâ€Assisted Grinding - Abulkhair Abdullah (LPPM Universitas Abdurrab, 2022)
Cocrystallization of mefenamic acid (AM) with para-aminobenzoic acid (PABA) as a coformer has been carried out using the liquid-assisted grinding method. This study aims to determine whether mefenamic acid can be increased its dissolution rate through the formation of cocrystals with PABA. Cocrystal AM-PABA were prepared in a 1:2 molar ratio. The dissolution rate of AM-PABA cocrystal was 1.45 times better than that of pure mefenamic acid. The formation of cocrystals was confirmed by characterization results which showed the formation of a new crystalline phase which was indicated by the appearance of new diffractogram peaks on XRD, decreasing melting point on DSC thermogram, and shifting and decreasing of wavenumber intensity in FTIR spectra.